Billiards: At the intersection of Physics, Geometry and Computer Algebra Systems - Vallejo, Jose A (The electronic journal of mathematics & technology, 2025)
We study the properties of billiards (mainly elliptical) as dynamical systems, in particular, their integrability, and the existence and computation of periodic orbits. An implementation of the involved computations in a free CAS (Maxima) is also presented, as a tool for visualization and experimentation, which can be useful in web-based courses and distance learning.